Strategi Komunikasi Politik Ideal bagi Calon Walikota Dalam Pilkada Aceh 2024 - Abda, Yusfriadi; Zulfikar (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Agama Islam (IAI) Al-Aziziyah Samalanga, 2024)
Effective political communication strategies play a vital role in the success of political contests, particularly in regions with strong cultural and religious characteristics such as Aceh. The 2024 Aceh Regional Election serves as a crucial opportunity for mayoral candidates to formulate communication approaches that align with local aspirations. This study aims to develop an ideal political communication strategy that resonates with Aceh's local values, encompassing traditions, religiosity, and societal dynamics. This research employs a qualitative approach with a case study method. Data were collected through in-depth interviews, direct observations, and related document analysis. Thematic analysis was conducted to identify key patterns in the application of political communication strategies in Aceh. The findings reveal that an ideal political communication strategy for mayoral candidates must integrate local values, such as the use of inclusive language, incorporation of religious values into campaigns, and dialogical approaches to actively involve the community. A combination of traditional methods, such as communal discussions, with modern technology like social media, also serves as a key element to reach diverse voter segments. This study offers practical and theoretical contributions by providing a culturally sensitive guide for designing relevant and effective political communication strategies.